A user perspective on future cloud-based services for Big Earth data. Issue 12 (2nd December 2021) - Wagemann, Julia; Siemen, Stephan; Seeger, Bernhard; Bendix, Jörg
ABSTRACT : Cloud-based services introduce a paradigm shift in how users access, process and analyse Big Earth data. A key challenge is to align the current state of how users access, process and analyse the data with trends and roadmaps large data organisations layout. In addition, due to the increased availability of open data, a more diverse user base wants to take advantage of Earth science data leading to new user requirements. We run a web-based survey among Big Earth data users to better understand the motivation to migrate to cloud-based services as well as the challenges and opportunities that might arise. Results show an overall interest in moving to cloud-based services but air an insufficient literacy in cloud systems and a lack of trust due to security concerns and opacity of emerging costs. These gaps demand efforts on three levels. First, cloud services shall be targeted at intermediate users instead of policy- and decision-makers and over-engineered systems with a high level of abstraction should be avoided. Second, more substantial capacity-building efforts are required to decrease the existing gap in cloud skills and uptake. Third, a cloud certification mechanism could help in building up overall trust in cloud-based services.